Diagnostic Efficacy of Vibration-Controlled Transient Elastography in Patients With Metabolic Dysfunction–Associated Liver Disease and Chronic Hepatitis B - Yaoyu Liu; Zhizhen Huang; Xinya Lan; Min Jia; Xiaoting Zheng; Min Hu; Huiying Luo; Luyun Zhang; Xuejing Li; Shaodong Chen; Yunru Li; Huiqing Liang (Gastroenterology Research and Practice, 2024)
Conclusion:In this investigation of adult patients diagnosed with CHB with MASLD, VCTE demonstrated a robust capability to differentiate cirrhosis and severe steatotic liver.